2015
DOI: 10.1111/andr.12030
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sperm DNA fragmentation index and CMA3 positive spermatozoa in globozoospermic patients

Abstract: SUMMARYThe absence of the acrosome causes the situation which is called globozoospermia. There are a few studies, mostly as case reports, about correlation between levels of sperm DNA damage in patients with total round-headed spermatozoa. We investigated this correlation as well as CMA3 positive spermatozoa in 20 globozoospermic men (with more than 90% round-headed spermatozoa) attending to Royan Institute. Semen samples divided into three parts to semen analysis, to measure DNA fragmentation index (DFI) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 56 publications
3
16
1
Order By: Relevance
“…However, we observed remarkably lower total motility, progressive motility, sperm count and normal morphology in both types of globozoospermic samples compared with normozoospermic controls ( p < .001) (Ghasemzadeh et al, ; Talebi et al, ) (Table ). In agreement with our results, Hosseinifar et al demonstrated significant decreases in sperm concentration, total motility and normal morphology in patients with globozoospermia compared with the controls ( p < .001) (Hosseinifar et al, ).…”
Section: Sperm Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…However, we observed remarkably lower total motility, progressive motility, sperm count and normal morphology in both types of globozoospermic samples compared with normozoospermic controls ( p < .001) (Ghasemzadeh et al, ; Talebi et al, ) (Table ). In agreement with our results, Hosseinifar et al demonstrated significant decreases in sperm concentration, total motility and normal morphology in patients with globozoospermia compared with the controls ( p < .001) (Hosseinifar et al, ).…”
Section: Sperm Parameterssupporting
confidence: 93%
“…This finding could be due to two reasons. Firstly, all three studies (Ghasemzadeh et al, ; Hosseinifar et al, ; Talebi et al, ) were performed according to WHO () standards, which presented lower cut‐off criteria compared with previously introduced WHO standards ( and ) (Table ). Secondly, these researches included 47 oligozoospermic patients, whereas most of the previous studies in this regard were case reports.…”
Section: Sperm Parametersmentioning
confidence: 99%
“…In the current study, mean percentage of protamine deficiency was lower than recent study(34% vs 49%) published by Hosseinifar et al. (). This difference could be due to low number of counted spermatozoa (100 vs 500) or low number of globozoospermic cases (20 vs 30).…”
Section: Discussioncontrasting
confidence: 77%
“…The difference between studies can be due to low number of globozoospermic cases, method of assessment, type of globozoospermia (total or partial) and etc. Recently, two studies demonstrated high rate of sperm DNA fragmentation and protamine deficiency in 20 and 15 partial globozoospermic patients (Ghasemzadeh et al., ; Hosseinifar et al., ). In light of these considerations, we decided to assess sperm protamine deficiency and DNA fragmentation in 30 men affected by total globozoospermia (100% round‐headed spermatozoa without acrosomes).…”
Section: Introductionmentioning
confidence: 99%
“…Only in one case (G12), the expression levels of these transcripts were close to fertile men, but AOA could not result in a good fertilization rate (17%) in this case. Different explanations can be provided for such a case including defective chromatin packaging or increased DNA fragmentation which has been thought to affect fertilization and pregnancy outcome of ICSI oocytes (De-Braekeleer et al, 2015;Hosseinifar et al, 2015). Yassine et al (2015) recently demonstrated that in globozoospermic mice and humans with deletion of DPY19L2, sperm devoid of an acrosome has altered genomic packaging and increased DNA damage which can compromise ICSI outcomes (Yassine et al, 2015).…”
Section: Discussionmentioning
confidence: 99%